2017
DOI: 10.1210/jc.2017-00191
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Glycation Index Is Associated With Cardiovascular Diseases in People With Impaired Glucose Metabolism

Abstract: High HGI was independently associated with overall and individual CVDs. This result suggests that discrepancy between HbA1c and fasting glucose levels can reflect vascular health in subjects with impaired glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 41 publications
3
51
2
Order By: Relevance
“…It was beyond the scope of our study to attempt to identify the frequency of mismatches in the population, although our design led to one‐third of our participants having a high HGI mismatch and one‐third with a low HGI mismatch, sufficient to lead to false‐positive and false‐negative diagnoses, respectively; additional studies should pursue this objective. Finally, although our mismatch metric, HGI, is established in the literature , it is glycaemia‐dependent . We attempted to compensate for this by using separate regressions for each OGTT group, and it may be necessary to use HGI when the number of glucose samples is limited; future studies are also needed to examine the impact of mismatches with a glycaemia‐independent metric such as CGM‐based estimation of mean red blood cell age .…”
Section: Discussionmentioning
confidence: 99%
“…It was beyond the scope of our study to attempt to identify the frequency of mismatches in the population, although our design led to one‐third of our participants having a high HGI mismatch and one‐third with a low HGI mismatch, sufficient to lead to false‐positive and false‐negative diagnoses, respectively; additional studies should pursue this objective. Finally, although our mismatch metric, HGI, is established in the literature , it is glycaemia‐dependent . We attempted to compensate for this by using separate regressions for each OGTT group, and it may be necessary to use HGI when the number of glucose samples is limited; future studies are also needed to examine the impact of mismatches with a glycaemia‐independent metric such as CGM‐based estimation of mean red blood cell age .…”
Section: Discussionmentioning
confidence: 99%
“…The HGI reflects the difference between measured HbA1c and predicted HbA1c, which is calculated from mean blood glucose levels using a linear regression equation. Some studies suggest that higher HGI levels are associated with diabetic complications, metabolic disease and cardiovascular disease …”
Section: Introductionmentioning
confidence: 99%
“…associated with diabetic complications, metabolic disease and cardiovascular disease. [3][4][5][6][7][8][9] Nonalcoholic fatty liver disease (NAFLD) is one of the most prevalent metabolic diseases worldwide. 10 It can progress to steatohepatitis, cirrhosis and even hepatocellular carcinoma, which is associated with high mortality rates.…”
mentioning
confidence: 99%
“…Recently, several studies have been performed to analyze the practical applicability of HGI measurements. A cross-sectional study demonstrated that high HGI levels signi cantly increased the risk of coronary artery disease, stroke, and peripheral artery disease in individuals with an impaired glucose metabolism [45]. The Kangbuk Samsung Health Study in Korean indicated that individuals with the highest HGI levels had a 1.722-fold risk of incident coronary artery calcium compared to the bottom group regardless of HbA1c levels [46].…”
Section: Discussionmentioning
confidence: 99%